Sustained circulation of genotype I and the first whole-genome sequencing of feline calicivirus in Turkish cats - Abayli, Hasan; Yalcinkaya, Ertug; Tonbak, Sukru; Aslan, Ahsen Nisa (Bmc, 2026)
This study was conducted to expand the limited knowledge regarding the detection, molecular characterization, and epidemiology of feline calicivirus (FCV) in Turkiye by examining viral pathogens associated with ulcerative stomatitis in cats. Analysis of forty clinical samples revealed twelve FCV-positive cases. Additional viral agents identified included feline chaphamaparvovirus (FChPV; n = 6), feline alphaherpesvirus 1 (FHV-1; n = 4), and feline panleukopenia virus (FPLV; n = 9), while no feline bocavirus (FBoV) or feline bufavirus (FBuV) infections were detected. Five coinfection events were recorded: FCV+FPLV (n = 2), FCV + FHV-1 (n = 1), FHV-1 + FPLV (n = 1), FCV + FChPV (n = 2), and FChPV + FPLV (n = 1). Of the FCV-positive samples, sequencing efforts focused on two representative isolates, yielding one complete genome and one partial virion protein 1 (VP1) sequence. Illumina-based whole-genome sequencing of an FCV-positive specimen yielded a complete 7,738-nucleotide (nt) genome comprising three open reading frames (ORFs): ORF1 (1,763 amino acids [aa]), ORF2 encoding the major capsid protein (VP1) (669 aa), and ORF3 encoding a small basic protein (106 aa). The FCV-TUR-2025-V isolate (PX601232) harbored a distinct two-amino acid insertion consisting of glycine and aspartic acid ( -GD) at VP1 positions 127-128, along with multiple substitutions within the virulence-associated region E. Comparative genomic analysis against 241 globally distributed FCV genomes demonstrated 77-82% nt identity, with the highest similarity observed to Chinese strains (FCV-AH3, FCV-GZ-VSD). VP1-based analyses revealed 74-81% nucleotide (nt) and 82-90% amino acid (aa) identity relative to reference strains. The highest sequence similarity was observed with strains from Korea (KS40), Japan (FCV-131 and FCV-187), the United Kingdom (Orf3), Italy (FCV/160/2015/ITA), and Thailand (KP82/THA/2016) (similar to 81% nt; similar to 89% aa). In addition, several U.S. isolates exhibited comparable levels of genetic relatedness to FCV-TUR-2025-V (79-80% nt; similar to 90% aa). Phylogenetic reconstruction using whole-genome and VP1 sequences identified two major genogroups (GI and GII), with all Turkish isolates clustering within GI. Among the Turkish strains, one isolate was represented by a whole-genome sequence (FCV-TUR-2025-V), while another was characterized based on the VP1 gene (FCV-TUR-2025-V2; PX601233). FCV-TUR-2025-V showed close clustering with recent Italian strains (FCV/460/20 - 1_RS; FCV/460/20 - 2; FCV/460/20 - 2_RS), whereas FCV-TUR-2025-V2 exhibited closer relatedness to the German isolate FCV/DD/2006/GE and the U.S. strain UTCVM-H2. Analysis of the E5 ' HVR region demonstrated that FCV-TUR-2025-V preserved the conserved B-cell epitope motif PAGDY (aa 431-435) and carried the ITTPQEY (aa 445-451) motif within the neutralizing epitope. In contrast, FCV-TUR-2025-V2 displayed the alternative motifs PTGNY (aa 431-435) and ITTRLDY (aa 445-451). These variations highlight notable epitope-level diversity with potential implications for altered antibody recognition and immune-escape mechanisms-particularly relevant given the occurrence of FCV infection in vaccinated cats. Overall, this study provides valuable insights into the molecular epidemiology of FCV in Turkiye and underscores the importance of continued genomic surveillance to better understand viral evolution, pathogenic potential, and vaccine-related breakthrough infections.
Keywords: Calicivirus; Chaphamaparvovirus; Co-detection; Feline; Sequencing; Turkiye; Whole-genome